ANALISIS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes), BERDASARKAN PERMENDAGRI NOMOR 20 TAHUN 2018, DI DESA AERAMO, KECAMATAN AESESA, KABUPATEN NAGEKEO (2018-2020) - Mariet Karolina Goo; Herni Sunarya; Maryono (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2021)
This study aims to determine the Management of the Village Revenue and Expenditure Budget (APBDes) in Aeramo Village, Aesesa District, Nagekeo Regency, in accordance with the Minister of Home Affairs Regulation Number 20 of 2018. This type of research is a case study research conducted in Aeramo Village, District Aesesa, Nagekeo Regency, East Nusa Tenggara. Data collection techniques can be done by means of interviews (interviews), documentation and observation (observations). Meanwhile, the data analysis techniques in this study were in the form of data collection, data reduction, data display, and conclusion drawing/verification. The results showed that: the stages of village financial management consisting of planning, implementation, administration, reporting and accountability had been implemented in Aeramo village well. The stages that are in accordance with the Regulation of the Minister of Home Affairs No. 20 of 2018 are the planning, implementation, reporting and accountability stages while the administrative stage is not in accordance with the Regulation of the Minister of Home Affairs No. 20 of 2018.